Study on soil erosion using 137Cs as environmental tracer in Fraser's Hill, Pahang, Malaysia / Ahmad Sanadi Abu Bakar - Abu Bakar, Ahmad Sanadi (2018)
The use of 137 Cs as tracer for soil erosion and redistribution studies is possible due to the fact that 137 Cs does not occur naturally and its affinity to adsorb to fine soil particles. Fraser's Hill is selected as the study area as there is no prior research of using 137Cs as environmental tracers for soil erosion studies. The analysis of 137Cs on surface soil and core soil was performed. using gamma spectrometry. The gamma spectrometer was calibrated, checked for background and tested for accuracy and precision. The accuracy of the spectrometer was a mean z-score of 0.3 and the precision was 5.20 ± 1.82 when tested against the IAEA-414 Standard Reference Material. The sampling was divided into two areas namely Developed Area and Undeveloped Area. Surface and core soils were sampled from both areas and tested for their physical properties. Their lithology, soil type, soil pH, bulk density, organic matter content, carbonate content, sand portion and caly portion were compared and found no statistically significant difference in the soil from both areas. The comparison however did find statistically significant difference in the water content and silt portion in the soil from both areas. The measurement of surface dose at 0 m and 1 m found statistically, significant difference in both areas with the Undeveloped Area exhibiting higher surface doses at 0 m and 1 m.